Challenges and Perceptions of Female Futsal Athletes on Gender Stereotype Issues - Wulan Sari; Bangbang Syamsudar; Suhada (Journal of Physical and Outdoor Education, 2026)
This study aims to explore female futsal athletes' challenges and perceptions of gender stereotyping issues. Female futsal athletes often face social, physical, and psychological barriers stemming from the assumption that futsal is a masculine sport. This research used descriptive qualitative method with purposive sampling technique, involving 5 female futsal athletes from Venus Independent club. The research instruments were observation, in-depth interviews, and photovoice to comprehensively reveal the experiences and views of athletes. The results showed that gender stereotypes exert social pressure and affect athletes' self-confidence, but athletes are able to develop adaptive strategies to deal with them, such as improving selfquality and proving abilities through achievement. This study concludes that although gender stereotypes are still a significant challenge, female futsal athletes show resilience in the face of discrimination and form positive perceptions of their role in futsal sport. This research is expected to contribute in strengthening support for gender equality in sport, especially in futsal.